Recent patterns of economic alignment in the European (Monetary) Union - Agnieszka Gehringer; Jörg König (Journal of Risk and Financial Management, 2021)
This paper studies the process of business cycle synchronization in the European Union and the euro area. As our baseline methodology we adopt rolling window correlation coefficients of various economic indicators, observed since 2000. Among the indicators, we distinguish between real economic indicators, like the real GDP growth and unemployment, and nominal indicators, like inflation and government budget. Given the direct implication of this kind of analysis for the common monetary policy of the European Central Bank (ECB), special attention is paid to the pattern of business cycle synchronization in the core and peripheral members of the euro area. Our analysis of quarterly data covering the first two decades of the euro area shows that there was a certain synchronization tendency in the first years of the common currency. However, the European debt crisis halted the economic integration within the European Union and - even more so - within the euro area. Since the ECB can to a large extent intervene only with "one-size-fits-all" monetary policy instruments, this renders increasingly cumbersome the conduct of stabilisation policies within the euro area.
Keywords: 330; business cycle synchronization; disintegration; economic integration; euro; European Union